The changing nature of international business relationships and foreign language competence. (15th November 2004) - Swift, Jonathan; Huang, Yuelu
This paper examines the role of Foreign Language Competence (FLC) in international business, at a time when business activity, in general, is becoming increasingly international, and when the focus of business relationships is changing from that of a short-term, task-orientated approach, to one of a longer-term relationship orientation. As a consequence of these changes, the authors suggest that FLC should become increasingly focused on the development/maintenance of long-term business relationships, rather than the traditional short-term "sales-orientation" which has been the case so far. The paper is a conceptual contribution, which will be empirically tested at a later date.